Seeking the Pattern Using Quantitative Text Analysis to Assess Text Influence on Grant Program Results - Valeš, Miroslav; Bruckner, Tomáš, 1974-; Ircing, Pavel; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2015)
Since software and hardware is well available for automated text analysis and since a large data that describes real projects submitted to grant program is opened up, there is a possibility to follow phenomena of behavioral economics and psycholinguistics which evidence particularities in textual descriptions may be statistically associated with a reader's behavior or with a reader's decision-taking, which, in this case, involves an influence on final allocation of grant funds. The thesis uses forenamed areas as a starting-point and also employs quantitative indicators from the field of forensic linguistics in order to perform a computer-aided quantitative text analysis. The main goal is to evaluate from correlation perspective, if there in real operational programmes were present any associable relationships between the quantitative features of a proposed project's textual description and the amount of grant allocated to a project. The thesis is divided into four chapters, where it introduces basis, describes analyzed data and used methods, comments on made analyses and found relations, and all the performed research is summarized and evaluated in the last chapter.
Vedoucí práce: Tomáš Bruckner
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: kognitivní informatika [obor dipl. práce]; diplomové práce; master's theses